2001
DOI: 10.1016/s0006-3495(01)75859-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dynamic Gap Junction Resistance on Impulse Propagation in Ventricular Myocardium: A Computer Simulation Study

Abstract: The gap junction connecting cardiac myocytes is voltage and time dependent. This simulation study investigated the effects of dynamic gap junctions on both the shape and conduction velocity of a propagating action potential. The dynamic gap junction model is based on that described by Vogel and Weingart (J. Physiol. (Lond.). 1998, 510:177-189) for the voltage- and time-dependent conductance changes measured in cell pairs. The model assumes that the conductive gap junction channels have four conformational stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 44 publications
(51 reference statements)
1
57
0
2
Order By: Relevance
“…12,19,20,43). In our study, we ignore coupling of oscillations by calcium and IP 3 diffusion for good reasons, which are explained in the DISCUS-SION.On the other hand, there is propagation of electrical activity in networks of cells electrically coupled by gap junctions, such as in the ventricular myocardium (17,18,(23)(24)(25)(26). In such types of cell networks, propagation of electrical activity is the result of depolarization of a cell by action potential (AP) firing of its neighbor.…”
mentioning
confidence: 99%
“…12,19,20,43). In our study, we ignore coupling of oscillations by calcium and IP 3 diffusion for good reasons, which are explained in the DISCUS-SION.On the other hand, there is propagation of electrical activity in networks of cells electrically coupled by gap junctions, such as in the ventricular myocardium (17,18,(23)(24)(25)(26). In such types of cell networks, propagation of electrical activity is the result of depolarization of a cell by action potential (AP) firing of its neighbor.…”
mentioning
confidence: 99%
“…Whether alternative approaches that have been proposed for the continuous loop would be more appropriate remains to be determined. [11,16,17] In any case, we are still far from a general low-dimensional model that could be applied in situations including a dynamic change of the intercellular coupling, as in [28,29,30].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Previous computational studies have indicated that the number of cells producing abnormal electrical activity is critical in determining whether a propagating extrasystole will be generated [20]. This idea is similar to the concept of liminal length in neuronal propagation.…”
Section: D Fibre -Central Ead Capable Regionmentioning
confidence: 91%